Investigation of Digital Game Addiction and Attitudes Towards Sports in Adolescent Individuals - Yusuf Burak Yamaner, Ümran Sarikan, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aimed to examine digital game addiction and attitudes towards sports in adolescents. Method: The screening model was used in our research. After giving preliminary information about the questionnaire to the participants, a total of 191 volunteers, 113 (59.5%) females and 77 (40.5%) males participated in the study voluntarily. In the research, the 'Digital Game Addiction Scale (DGAS-7) and the 'Sports Attitude Scale ' (5-point Likert Type) consisting of 22 items were used as data collection tools. The research data were analyzed with the SPSS 22.0 package program and the margin of error was taken as p<0.05. Results: When the results were examined, it was seen that 59.5% of the participants were women, 40.5% were men, and 45.8% participated in the exercise activity. At the same time, it was understood that the total scores of psychosocial development, mental development and attitude towards sports, which were sub-dimensions of the sports attitude scale, of the participants who exercise had higher scores than the participants who did not exercise. In this context, it can be said that the attitudes of the participants who exercise were more meaningful. Conclusion: As a result, young adult individuals who were connected to games may have difficulties in fulfilling their daily responsibilities and may cause mental and cognitive disorders as a result of establishing a connection between real life and the virtual world, which can negatively affect their academic achievement levels. Moreover, individuals should be encouraged to participate in sports, because it was thought to have a positive effect on the mental and physical development of young adults. Keywords: Adolescent, Sports and Digital Game This Research Was Present at as Oral Presentation the 8th International Congress on Science, Culture and Sports